Rethinking multicultural education : case studies in cultural transition - Korn-Bursztyn, Carol, 1953-; Bursztyn, Alberto, 1952- (Bergin & Garvey, 2002)
Korn and Bursztyn and their contributors examine the cultural transitions that children make as they move between home and school. Case studies present instances of how diversity engages us in renegotiating the personal and social. In illuminating the complicated nature of cultural transitions, they highlight how multiculturalism can play a transformative role in the lives of children and schools.